(untitled) (International Journal of Engineering and Computer Science, 2014)
This paper presents basic about Virtual Private Network (VPN). In this paper, we can basically focus on its Types, Architecture, Functionality and Protocols. A ”VIRTUAL PRIVATE NETWORK” is an authenticated and encrypted communication channel across some form of public network, such as internet. The concept of “VIRTUAL PRIVATE NETWORK” is utilized by almost 60% of firms, companies and organizations to communicate each other.